Coercion and the credibility of assurances - Cebul, MD; Dafoe, A; Monteiro, NP (University of Chicago Press, 2021)
What makes coercion succeed? For most international relations scholars, the answer is credible threats. Yet scholars have neglected a second key component of successful coercion: credible assurances. This article makes two contributions to our understanding of coercion and credible assurances. First, we offer a theoretical framework exploring the causes and consequences of assurance credibility. In order to coerce the target, a challenger must issue both credible threats that defiance will be met with punishment, and credible assurances that compliance will be met with restraint. In turn, the credibility of assurances is determined by power and a reputation for restraint. Whereas greater power boosts credible threats, it undermines credible assurances. Therefore, powerful states must cultivate a reputation for restraint in order to issue credible assurances. Second, we provide empirical support for our claims through a nationally representative, scenario-based survey experiment that explores how US citizens respond to a hypothetical coercive dispute with China.